Mechanics and microstructure of deformed natural anisotropic ice. (October 2018) - Craw, Lisa; Qi, Chao; Prior, David J.; Goldsby, David L.; Kim, Daeyeong
Abstract: We deformed coarse-grained (∼10 mm) natural ice in axial compression at −30 °C, to an axial strain of 0.2, at three different angles to the existing strong crystallographic preferred orientation (CPO). We used three strain rates for each sample orientation. Cryo-electron backscatter diffraction (EBSD) maps show that after deformation there is a mixture of large (∼1–2 mm) relict grains, and finer (100–200 μm) recrystallised grains. The fine grains form a connected network in all samples. The large grains define a very strong CPO with equivalent but weaker CPOs in the recrystallised grains. The final CPO changed completely from its original orientation. Lattice distortion and subgrains equivalent in size to recrystallised grains suggest a subgrain rotation recrystallisation process has generated the recrystallised fraction. We suggest that strain rates were higher in the connected network of recrystallised grains because of a significant component of grain boundary sliding (GBS) that enables large grains to rotate by a combination of glide on the basal plane and rigid rotation, to define a very strong CPO. GBS weakens the CPO in the finer grained regions. The patterns of mechanical behaviour and the resultant microstructures do not bear an obvious relationship to original CPO. Graphical abstract: Image 1 Highlights: Natural ice samples compressed at −30 °C change CPO completely within strains of 0.2 Small (100–200 μm) grains form an interconnected network around large (1–2 mm) grains. CPOs are weaker in smaller grains than in larger grains. There is no obvious relationship between mechanical behaviour and initial CPO.